Pengaruh Loan To Deposit Ratio (LDR) Dan Non Perfoming Loan (NPL) Terhadap Harga Saham Pada PT Bank Negara Indonesia (Persero) Tbk Periode 2013-2022 - Fadilah, Farah; Muhamad Nurhamdi; Nina Shabrina; Rita Satria (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to determine the effect of Loan to Deposit Ratio (LDR) and Non-Performing Loans (NPL) on stock at PT Bank Negara Indonesia (BNI) Tbk for 2013-2022. This research uses 2 (two) independent variables That is Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) and 1 (one) dependent variable stock's price. This research is using quantitative methods, data analysis uses descriptive statistical techniques, classical assumption tests, multiple linear regression, hypothesis testing and coefficient of determination. Data processing uses SPPS 26 software. Based on test results on variables with 10 years of data. The Multiple Linear Regression Test Equation is Y = 19,248.185 – 106.314X1 – 1,563.302X2. In the coefficient of determination test, it was found that the influence of LDR and NPL on share prices was 10%, while the remaining 90% was influenced by other factors. Based on the results of the t test, tcount for LDR was 0.612 < ttable 2.365 and the value of Sig. 0.560 > 0.05 means that there is no partial significant influence between LDR on share prices. and NPL tcount of 0.872 < ttable 2.365 and Sig value. 0.412 > 0.05, which means that there is no partial significant influence between NPL on share prices. In the simultaneous test the LDR and NPL variables do not have a significant effect on share prices with Fcount being smaller than Ftable (0.693 < 4.74).